Corporate Social Responsibility and Financial Performance: Insights from Manufacturing Firms Listed on the IDX - Nuraini, Ani; Nurhastuti, Tiwi; Maya Sova; Ismaya, Sakti Brata (Majalah Ilmiah Bijak, 2025)
CSR is also a program aimed at achieving sustainable development goals, as in this case, the company not only seeks benefits in terms of profits and tax contributions to the government but also provides benefits to society and the environment, especially during the COVID-19 pandemic. Objective: To understand and analyze the effect of CSR on financial performance in DER, to understand and analyze the effect of CSR on financial performance in GPM, and to understand and analyze the effect of CSR on financial performance in NPM. Method: This research is quantitative in nature, testing hypotheses on the causal effects between variables, using panel data regression analysis. The data used are secondary time series and cross-sectional data from 2015 to 2019 for 7 manufacturing companies listed on the Indonesia Stock Exchange (BEI), with model selection based on alternatives of common effect, fixed effect, and random effect. Results: The study concludes that for the independent variable DER, the best model is REM, while for the GPM variable, the best model is FEM, and for the NPM variable, the best model is CEM. Furthermore, the significant test results show that CSR significantly reduces DER, while CSR also has a significant impact on financial performance in generating both gross profit and net profit relative to sales.Recommendation: Based on the research findings, it shows that CSR contributes to financial performance, making it easier for companies to attract investors to further develop the company and provide benefits for stakeholders